1975
DOI: 10.1111/j.1744-313x.1975.tb00541.x
|View full text |Cite
|
Sign up to set email alerts
|

PASSIVE ENHANCEMENT OF H‐2 INCOMPATIBLE SKIN ALLOGRAFTS AND MLR INHIBITION BY CROSS‐REACTIVE Ia ANTIBODIES

Abstract: Passive enhancement of H-2 incompatible skin allografts was studied in systems where the enhancing serum covered only a restricted number of Ia specificities involved in the incompatibility. Sera reacting with products of the I-A legion were effective at prolonging survival, probably to the same extent as a serum covering all the specificities of the incompatibility. Such sera also inhibited MLR in the same strain combinations. Interpretation of these and other data suggests that products of the I-B, I-E and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The possible role of the I region in these studies was discussed in an earlier paper (McKenzie & Henning, 1977). Our findings confirm the extensive studies of Staines et al (1974Staines et al ( , 1975 who removed K region activity from an enhancing antiserum directed against K and I region specificities by absorption with red cells or platelets, leaving only I region activity which could still produce enhancement for the K + I region incompatibility. This group found similar results for rat heart allograft (Davies & Atkins, 1974) and similar findings have been reported for rat renal allografts (Soulillou et al, 1976).…”
Section: Discussionsupporting
confidence: 89%
“…The possible role of the I region in these studies was discussed in an earlier paper (McKenzie & Henning, 1977). Our findings confirm the extensive studies of Staines et al (1974Staines et al ( , 1975 who removed K region activity from an enhancing antiserum directed against K and I region specificities by absorption with red cells or platelets, leaving only I region activity which could still produce enhancement for the K + I region incompatibility. This group found similar results for rat heart allograft (Davies & Atkins, 1974) and similar findings have been reported for rat renal allografts (Soulillou et al, 1976).…”
Section: Discussionsupporting
confidence: 89%
“…The authors found identical specific inhibition of MLR cultures with la sera prepared by RBC absorption when they are either used to pretreat stimulator cells before establishing the cultures or are added to the cultures themselves. The authors have also found some evidence that third-party MLR combinations are also partly inhibitable by la sera of restricted serological cross-reactivity with the stimulator cell type (Staines et al 1975b). This parallels the prolongation of graft survival in the same system in vivo (see above).…”
Section: Inhibition Of Mlr By La Antisera and Its Relationship To Iymmentioning
confidence: 94%